Contribution of time management and locus of control on student academic prograstination - Muhammad Sulaiman; Syahniar Syahniar; Daharnis Daharnis (International Conferences on Educational, Social Sciences and Technology)
This study aims to determine the contribution of time management to student academic procrastination, contribution of locus control to student academic procrastination, and contribution of time management and locus of control to academic procrastination of UMSU Medan students. Types of quantitative research correlational approaches. The population are 180 undergraduate students of UMSU Medan. Sample 124 people with stratified proportional random sampling technique. The instrument used is Likert scale. The reabilty of instrument 0,955. Research data were analyzed by simple regression and multiple regression. The result of the research shows that the ability of time management with medium category, the tendency locus of control with medium category, low academic procrastination level, time management contribute significantly to academic procrastination, locus of control contribute significantly to academic procrastination, time management and locus of control jointly contribute 20,6% significantly to the academic procrastination of students at UMSU Medan.